Prevalence and factors associated with adverse drug events among patients on dolutegravir‑based regimen at the Immune Suppression Syndrome Clinic of Mbarara Regional Referral Hospital, Uganda: a mixed design study - Namulindwa, Angella; Wasswa, John Hans; Muyindike, Winnie; Tamukong, Robert; Oloro, Joseph (AIDS Research and Therapy, 2022)
Background: In low income countries such as Uganda progress has been made towards achieving the United Nations AIDS programme 95-95-95 target however efforts are still impeded by pretreatment drug resistance and adverse drug events (ADEs) hence introduction of dolutegravir-based antiretroviral therapy as first-line treatment due to a higher genetic barrier to resistance, better tolerability and safety profile. However, recent studies have raised concerns regarding its safety in real-clinical settings due to ADEs and being a recently introduced drug there is need to actively monitor for ADEs, hence this study aimed to establish the prevalence and factors associated with ADEs among patients on dolutegravir-based regimen at the Immune Suppression Syndrome (ISS) Clinic- Mbarara Regional Referral Hospital (MRRH). Methods: A mixed design study was conducted at ISS Clinic-MRRH among 375 randomly selected patients who had been exposed to DTG-based regimen for at-least 12 weeks. These were interviewed to obtain data on sociodemographics, dietary habits and their files reviewed for ADEs. Data entry was done using Epi-data 3.0 and exported to SPSS 25.0 for analysis. Prevalence was determined as a percentage, and ADE associated factors assessed using bivariate analysis, those found significant were further subjected to multivariate analysis and considered significant at P < 0.05. Results: The prevalence of ADEs among patients on DTG-based regimen was found to be 33.1% (124/375) with 5.6% (7/124) participants discontinued from treatment due ADEs, 4 due to hyperglycemia and 3 liver toxicity. The commonly experienced ADE was allergy at 36.3%. Male sex (AOR 1.571, 95% CI 1.433–1.984), WHO stage one at entry to care (AOR 4.586, 95% CI 1.649–12.754), stage two (AOR 4.536, 95% CI 1.611–12.776), stage three (AOR 3.638, 95% CI 1.262–10.488), were significantly associated with ADEs. Patients with undetectable viral load at initiation of DTG-based regimen were 67.6% less likely to experience ADEs (AOR = 0.324, 95% CI 0.1167–0.629). Conclusion: This study reports a prevalence of 33.1% of ADEs among patients on DTG-based regimen. The most commonly experienced ADE was allergy. Male sex, early HIV disease stage at entry into care and detectable viral load at initiation of DTG-based regimen were significantly associated with ADEs. It is crucial to actively monitor patients with these characteristics for ADEs.
Keywords: Dolutegravir-based; Adverse drug events; HIV; Uganda